Red. prof. dr. Emil Tokarz – sedemdesetletnik - Jesenšek, Marko; Będkowska-Kopczyk, Agnieszka (Slavia Centralis, 2020)
The article covers a description of life and work of prof. dr. Emil Tokarz and his extensive bibliography.
Keywords: Emil Tokarz; celebrations; Polish Slovenes; Polish Slavists; biographies; bibliographies; linguists